AN ECONOMIC STUDY TO SHOW THE EFFFECT OF VARIABLES (EDUCATION, HEALTH AND INDIVIDUAL SHARE OF PER-CAPITA) IN INCREASING AGRICULTURAL CROPS PRODUCTIVITY - Adnan A. Thalaj (Mesopotamia Journal of Agriculture)
The study depended on a hypothesis which says that variables of human development (Education, Health and Individual share of per-capita) have a great role in increasing agricultural crops productivity in a number of developing countries and in order to prove this hypothesis, A sample has been chosen from these countries by using theoretical style depending on previous studies and the quantitative style in measuring and analyzing the effect of human development variables . Cross section data has been used for the period (2002-2004) with the current prices . Throughout the study, we got the following results . Spending variable on health (X1) in effecting barley productivity in 2nd group states and its significant effect was in 1st and 3rd groups . This effect did not appear in productivity of barley crop . This effect appeared in values of agricultural product and in the states of 1st and 2nd groups . It disappeared in states of 3rd group . While, the significant effect appeared in spending variable of education (X2) in increasing wheat productivity in states of 1st and 3rd groups and it disappeared in states of 2nd group . The effect appeared in increasing barley productivity in the three groups . It disappeared in values of agricultural product and in the three international groups . The significant effect for the variable of median share of per-capita (X3) in productivity of wheat crop in both 1st and 2nd groups . It also appeared in the increase of agricultural product values and in all three international groups .